Time Management Of Teachers And Its Relationship To Teaching Performance - Olivo, Marylin G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This was a descriptive-correlational applied research which determined and analyzed the time management strategies of public elementary teachers in a district. The time management strategies of the teachers were related to their teaching performance. There were 103 elementary teachers in a district as respondents of the study. Since all teachers in the district were included as respondents of the study, the complete enumeration technique was employed as sampling technique. A time management questionnaire was developed by the researcher based on the activities that teachers need to accomplish and distributed with the help of the principals. The teachers indicated how many hours they spent on a particular task on a 24-hour basis. Weighted mean was used in analyzing the data on time management and Pearson R for the relationship of the time management of teachers and their teaching performance. Findings revealed that teachers were mostly very satisfactory in rendering their work, classroom teaching got the greatest number of time allotment among the teachers, teachers’ time management strategies ranged from using the internet for their needs in teaching to listing important tasks for the day to planning before classes start and working overtime at home to do tasks, work delegation was observed to be the least in their strategies to manage time. Furthermore, findings in this study showed that the teaching performance ratings of the teachers were not influenced by their time management strategies. It could be the tendency because most teachers had very satisfactory ratings. No one got satisfactory rating and only 12 were outstanding. If time management was not a factor, as the relationship test showed acceptance of null hypothesis, then the factor that determined or predicted teaching performance should be explored. The research then recommend that teachers should keep up with their positive teaching performance by giving the same passion and commitment towards work, they must continue giving most of their time in school to classroom instruction in order to produce pupils who are imbued with right values and knowledge and skills competence and they must embrace the challenge of the work responsibilities inherent to being a teacher. Teachers had practiced good time management because they allotted more time to classroom teaching and preparations to their core tasks as teachers. An action plan was developed to strengthen and sustain the time management strategies of teachers